Improving Education Quality Through Madrasa Committee Management in Indonesia - Agus Gunawan; Yuyun Rohmatul Uyuni; Muhamad Fauzi (International Journal of Emerging Issues in Islamic Studies, 2022)
Islamic education institutions in Indonesia, with a Muslim population majority, create a quality focus on education development in realizing the national character and sustainable development goals (SDGs), whereas the goal is creating education for all and equity. Need to realize quality education has built on the strengthening of madrasah committees according to religious ministry policy number 16 /2020 about madrasa committee as stakeholder participation applied during the Covid-19 pandemic with various limitations. Madrasa committee management being an independent, professional and modern principal, is an essential instrument in providing educational quality services to community needs. The weakness and less contribution of duties and functions as the madrasa committee becomes inhibits instrument to Islamic education quality achievement, and it is crucially this research. The objective of the research describes the strengthening of madrasah committee management to improve education quality. A research method is using a mix-method with a concurrent triangulation approach, research locations at state madrasa in Banten Province of Indonesia with interview and observation instruments. The results show that madrasa committee management is improving the management, especially for organizing, implementation and supervision. The committee's duties are providing financial support, thoughts, and staff for administering madrasa education, developing madrasa cooperation, supervising the implementation and management of education, and receiving and following up on complaints, suggestions, criticisms, and aspirations from students, parents, and the community. Sustainable development goals imply efforts to improve education quality through the madrasa committee management as public social participation.